Application of Swallow Fertilizer Combined with NPK Fertilizer on the Growth and Yield of Cucumber Plants - Yohanes Parlindungan Situmeang; Ni Putu Anom Sulistiawati; I Putu Adi Masaji (Agriwar Journal, 2023)
This study aims to determine the dosage of Swallow fertilizer and the dose of NPK fertilizer on the growth and yield of cucumber plants. This study used a randomized block design (RBD) in a factorial pattern with 2 treatment factors, namely: The first factor was swallow fertilizer consisting of 4 treatment levels, namely: without fertilizer, 10 tons ha-1, 20 tons ha-1, 30 tons ha-1, The second factor is NPK fertilizer consisting of 4 treatment levels, namely: without fertilizer, 150 kg ha-1, 300 kg ha-1, and 450 kg ha-1. Treatment of swiftlet fertilizer doses showed a significant to a very significant effect on all variables observed except for fruit dry weight per plant which had no significant effect. The highest yield of fresh fruit weight reached 732.67 g obtained in the swiftlet fertilizer treatment of 30 tons ha-1. NPK fertilizer dose treatment showed a very significant effect on all observed variables except for the variable cucumber flower exit time, cucumber fruit exit time, fruit dry weight per plant, and dry fruit weight per plant had no significant effect. The yield of fresh fruit weight reached 665.57 g obtained in the NPK fertilizer treatment of 150 kg ha-1. The interaction between swiftlet fertilizer dose and NPK fertilizer dose showed results that had a significant to a very significant effect on all variables observed except for the non-significant effect obtained on the cucumber fruit discharge time and fresh fruit weight per plant. Recommendations for swiftlet fertilizer 30 tons ha-1 and NPK fertilizer 150 kg ha-1 can be used to increase cucumber yields. Keyword: Organic fertilizer, swallow droppings, NPK fertilizer, cucumber.